Descriptive anatomy of the largest known specimen of Protoichthyosaurus prostaxalis (Reptilia: Ichthyosauria) including computed tomography and digital reconstruction of a three-dimensional skull - Dean R. Lomax; Laura B. Porro; Nigel R. Larkin (PeerJ, 2019)
Ichthyosaur fossils are abundant in Lower Jurassic sediments with nine genera found in the UK. In this paper, we describe the partial skeleton of a large ichthyosaur from the Lower Jurassic (lower Sinemurian) of Warwickshire, England, which was conserved and rearticulated to form the centrepiece of a new permanent gallery at the Thinktank, Birmingham Science Museum in 2015. The unusual three-dimensional preservation of the specimen permitted computed tomography (CT) scanning of individual braincase elements as well as the entire reassembled skull. This represents one of the first times that medical imaging and three-dimensional reconstruction methods have been applied to a large skull of a marine reptile. Data from these scans provide new anatomical information, such as the presence of branching vascular canals within the premaxilla and dentary, and an undescribed dorsal (quadrate) wing of the pterygoid hidden within matrix. Scanning also revealed areas of the skull that had been modelled in wood, clay and other materials after the specimen’s initial discovery, highlighting the utility of applying advanced imaging techniques to historical specimens. Additionally, the CT data served as the basis for a new three-dimensional reconstruction of the skull, in which minor damage was repaired and the preserved bones digitally rearticulated. Thus, for the first time a digital reconstruction of the skull and mandible of a large marine reptile skull is available. Museum records show the specimen was originally identified as an example of Ichthyosaurus communis but we identify this specimen as Protoichthyosaurus prostaxalis. The specimen features a skull nearly twice as long as any previously described specimen of P. prostaxalis, representing an individual with an estimated total body length between 3.2 and 4 m.